Chain extension of virgin and recycled polyethylene terephthalate. (April 2016) - Tavares, Albaniza A.; Silva, Diêgo F.A.; Lima, Poliana S.; Andrade, Daniela L.A.C.S.; Silva, Suédina M.L.; Canedo, Eduardo L.
Abstract: This study aims to evaluate the influence of a multifunctional epoxidic oligomer (Joncryl Polyad PR 002), commercialized as a chain extender for condensation polymers such as polyethylene terephthalate (PET), on the increase of PET molar mass and, consequently, on restoring its rheological properties. Virgin (PETV) and recycled (post-consumer) (PETPC) polymers were processed in a laboratory internal mixer, with and without the incorporation of the additive at different levels. The samples were characterized by torque and parallel-plate rheometry. According to the results, both PETV and PETPC melts behave as Newtonian fluids at the test conditions used. From torque and temperature measurements obtained from the internal mixer, it was possible to assess the molar mass changes. The estimates based on real-time torque measurements are fast and accurate indicators of the effectiveness of chain extension in PET, and that the incorporation of Joncryl Polyad PR 002 additive to PETV and PETPC has a strong influence on the increase of their molar mass.